2022
DOI: 10.1038/s43705-022-00162-z
|View full text |Cite
|
Sign up to set email alerts
|

Functionally diverse microbial communities show resilience in response to a record-breaking rain event

Abstract: Estuaries provide many ecosystem services and host a majority of the world’s population. Here, the response of microbial communities after a record-breaking flood event in a highly urbanized estuary was followed. Hurricane Harvey (hereafter Harvey) was a category 4 hurricane that made landfall on the Texas coast in 2017 and lashed the Houston area with 1.4–1.7 × 1010 m3 of rainfall, disrupting the natural gradients of nutrients and salinity. Here, we utilized metagenomics to analyze how Harvey altered the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…6). These shifts in physiology align with ndings on the genomic potential of the microbial community (Walker et al 2022). Brie y, using KEGG classi cations, they found that genes associated with common photosynthetic processes (photosystems I and II, cytochrome b6f, and photosynthetic antenna proteins) decreased and never fully recovered to pre-Harvey levels.…”
Section: Community Dynamicssupporting
confidence: 68%
See 2 more Smart Citations
“…6). These shifts in physiology align with ndings on the genomic potential of the microbial community (Walker et al 2022). Brie y, using KEGG classi cations, they found that genes associated with common photosynthetic processes (photosystems I and II, cytochrome b6f, and photosynthetic antenna proteins) decreased and never fully recovered to pre-Harvey levels.…”
Section: Community Dynamicssupporting
confidence: 68%
“…While it appears that in some cases phytoplankton communities can quickly return to their original composition and abundance, their resilience, or their ability to recover after a pulse disturbance requires further study (Shade et al 2012;Huang et al 2021). Important characteristics of resilient microbes (bacteria, archaea, phytoplankton) are thought to be dormancy, speciation rates, horizontal gene transfer, community composition, functionality (e.g., Philippot et al 2021;Walker et al 2022), while environmental characteristics in estuaries such as water residence times, distance from in ows and magnitude/duration of river discharge are often examined (Roelke et al 2013; Pinckney et al 2017;Paerl et al 2019). It has been observed amongst bacteria that there are dominant "core" taxonomic and functional groups that remain in ecosystems despite changes induced during disturbances (Kurm et al 2019; Walker et al 2022); this is one form of community resilience which can be measured quantitatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variegate functional composition of a microbiota should be preserved to make the community capable of facing environmental perturbations (Walker et al, 2022). Some measurables are needed to define the relationship between ecosystem function and diversity.…”
Section: Genes Taxa and The Microbial Diversitymentioning
confidence: 99%